Mothers’ experiences of mistreatment during childbirth – A qualitative analysis of patient insurance claims in Finland - Lamminpää, Reeta; Axelin, Anna; Härkänen, Marja; Männistö, Maija; Welling, Maiju; Lojander, Jaana (Elsevier, 2026)
Background
Mistreatment during childbirth by healthcare professionals is a recognized global issue, yet evidence from formal reporting systems such as patient insurance claims in high‑income settings like Finland remains limited.
Aim
To describe mothers’ experiences of mistreatment during childbirth in Finland as documented in patient insurance claims submitted to the Patient Insurance Centre.
Methods
This qualitative descriptive study analyzed 48 obstetric patient insurance claims in which mothers reported mistreatment during childbirth between 2012 and 2022. None of these claims resulted in compensation. In these claims, mothers provided self-authored narratives describing mistreatment as a contributing factor to the alleged patient injury. Data were analyzed using inductive content analysis. Background variables were summarized descriptively.
Findings
The unifying category, “Disrespectful maternity care and the violation of personhood,” encompassed two forms of mistreatment identified in the claims: disrespectful and controlling staff behavior and objectification and dismissal. Most mothers reported psychological harm, while some also described physical injuries such as perineal tears and infections attributed to mistreatment.
Discussion
Mistreatment emerged as a concern within a high-performing health system, with mothers describing disrespectful maternity care that they perceived as violating their personhood. Mistreatment alone is not compensable without a legally defined patient injury. This gap highlights the need for mechanisms that better address relational and emotional harm in maternity care.
Conclusion
Mistreatment should be recognized as a quality-of-care issue, and systemic efforts, including education and organizational support, are needed to ensure respectful, supportive, and safe childbirth experiences for all mothers.